2004
DOI: 10.1021/tx049831z
|View full text |Cite
|
Sign up to set email alerts
|

Contact Allergens Formed on Air Exposure of Linalool. Identification and Quantification of Primary and Secondary Oxidation Products and the Effect on Skin Sensitization

Abstract: Linalool (3,7-dimethyl-1,6-octadien-3-ol) is an important fragrance chemical, frequently used in scented products because of its fresh, flowery odor. Linalool is an unsaturated hydrocarbon and is therefore susceptible to oxidation in the presence of air. The primary oxidation products, that is, hydroperoxides, formed in the autoxidation process, are reactive compounds that can be suspected to act as sensitizers. In the present investigation, we studied the autoxidation of linalool with emphasis on the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
238
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(263 citation statements)
references
References 28 publications
18
238
1
5
Order By: Relevance
“…The concentration of geraniol started to decrease immediately on air exposure at room temperature. The rate of autoxidation was similar to that of linalool (3), that is, 80% of geraniol remained at 10 weeks of air exposure, whereas 20% remained at 45 weeks (Figure 2). The oxidation mixture polymerized with time, and the samples taken out beyond 45 weeks were no longer suitable for HPLC or GC analysis because of their viscosity.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…The concentration of geraniol started to decrease immediately on air exposure at room temperature. The rate of autoxidation was similar to that of linalool (3), that is, 80% of geraniol remained at 10 weeks of air exposure, whereas 20% remained at 45 weeks (Figure 2). The oxidation mixture polymerized with time, and the samples taken out beyond 45 weeks were no longer suitable for HPLC or GC analysis because of their viscosity.…”
Section: Resultsmentioning
confidence: 65%
“…Hydrogen peroxide is a well-known irritant, and the dose-response curve reflects its toxicity. The mixture of hydroperoxides 6 and 11 (5:3) was found to be strongly allergenic with an EC3 value of 0.077 M. The potency of these hydroperoxides is in the same range as that shown for the corresponding mixture of linalool hydroperoxides (3,15,29). According to our experience so far, all hydroperoxides tested show an EC3 value of 1% (15,29).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…38,39 Além desta, foi demonstrado que a auto-oxidação do linalol [4], pela sua exposição ao oxigênio do ar, também conduz ao óxido de linalol [6]. 40 A isomerização do GPP [1], obtida com a migração do grupamento difosfato do C1 para o C3, resulta no difosfato linalílico (LPP) [7]. A subseqüente rotação da ligação C2-C3 e ionização resultam no isômero do cátion linalíco [2'], que difere do primeiro por apresentar características espaciais favoráveis à ciclização molecular.…”
Section: Resultsunclassified
“…European legislators have become increasingly aware of the allergenic properties of many common essential oil constituents, and in 2003, the 7th Amendment to the European Cosmetic Directive required that cosmetic products containing any of 26 natural products, including linalool, be labeled as potentially allergenic [20]. While linalool itself may have limited allergenic properties, it can auto-oxidize upon air exposure into a hyperoxide species [21] which can lead to contact allergy responses in mice [22]. In a study of 1511 dermatitis patients, auto-oxidized linalool was shown to induce allergenic responses in 1.3 % of those tested, with 1.1 % of patients sensitive to the linalool hyperoxide fraction, using patch tests [23].…”
Section: Studies In Human Subjectsmentioning
confidence: 99%